2021
DOI: 10.1016/j.ibneur.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subanesthetic intravenous ketamine infusion on neuroplasticity-related proteins in male and female Sprague-Dawley rats

Abstract: Although ketamine, a multimodal dissociative anesthetic, is frequently used for analgesia and treatment-resistant major depression, molecular mechanisms of ketamine remain unclear. Specifically, differences in the effects of ketamine on neuroplasticity-related proteins in the brains of males and females need further investigation. In the current study, adult male and female Sprague-Dawley rats with an indwelling jugular venous catheter received an intravenous ketamine infusion (0, 10, or 40 mg/kg, 2-h), starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…Administration of ketamine was shown to enhance the release of dopamine and glutamate in the brain striatal region (Hons et al, 2010). Ketamine, an NMDAR antagonist induces hyper locomotion by increasing the number of lines crossed and reducing the ambulation time in mice (Sartim et al, 2021;Zhang et al, 2021). The crude extract of Cissampelos owariensis alongside its fractions were screened for their effect on behavioural studies.…”
Section: Bioactivity Of Crude Extract/fractions/compoundmentioning
confidence: 99%
“…Administration of ketamine was shown to enhance the release of dopamine and glutamate in the brain striatal region (Hons et al, 2010). Ketamine, an NMDAR antagonist induces hyper locomotion by increasing the number of lines crossed and reducing the ambulation time in mice (Sartim et al, 2021;Zhang et al, 2021). The crude extract of Cissampelos owariensis alongside its fractions were screened for their effect on behavioural studies.…”
Section: Bioactivity Of Crude Extract/fractions/compoundmentioning
confidence: 99%
“…We also observed delayed recovery of omission performance following ketamine emergence. In both human ( Ionescu et al, 2018 ) and rodent ( Radford et al, 2018 ; Zhang et al, 2019 , 2021 ) studies, even a single sub-anesthetic dose of ketamine has been shown to produce persistent changes in neural plasticity. Like dexmedetomidine, ketamine is typically administered in low doses as an adjunct with other general anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Different bolus doses were found to induce the protein expression of c-Fos in the amygdala of female rats, not the male rats. Also, in the prefrontal cortex, this expression was modulated by the estrous cycle [61]. The administration of ketamine in female mice exposed to chronic unpredictable mild stress was reported to be mediated via the extracellular-signal-regulated kinase and glucose transporter 3 (ERK/GLUT3) signaling pathway [62].…”
Section: Ketamine Sexually Dimorphic Antidepressant Effectsmentioning
confidence: 99%